1999
DOI: 10.1161/01.res.85.11.1056
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Electrode–Induced Reexcitation

Abstract: Abstract-Mechanisms of defibrillation remain poorly understood. Defibrillation success depends on the elimination of fibrillation without shock-induced arrhythmogenesis. We optically mapped selected epicardial regions of rabbit hearts (nϭ20) during shocks applied with the use of implantable defibrillator electrodes during the refractory period. Monophasic shocks resulted in virtual electrode polarization (VEP). Positive values of VEP resulted in a prolongation of the action potential duration, whereas negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…The ability to correct HV block in both these scenarios suggests that the intra-Hisian lesion causing HV block is fairly discrete, and virtual electrode polarization created during pacing is able to capture the His beyond the site of block. 22,23 In the series of HBP in infranodal AV block, we reported two patients with split His potentials. A similar clinical scenario was noted during the acute HV block induced during HBP in two patients where split His potentials developed following lead fixation ( Figure 4).…”
Section: Mechanistic Insightsmentioning
confidence: 99%
“…The ability to correct HV block in both these scenarios suggests that the intra-Hisian lesion causing HV block is fairly discrete, and virtual electrode polarization created during pacing is able to capture the His beyond the site of block. 22,23 In the series of HBP in infranodal AV block, we reported two patients with split His potentials. A similar clinical scenario was noted during the acute HV block induced during HBP in two patients where split His potentials developed following lead fixation ( Figure 4).…”
Section: Mechanistic Insightsmentioning
confidence: 99%
“…The virtual cathode serves as an electrical stimulus eliciting a regenerative depolarization and a propagating wave in the newly created excitable area. Whether or not break excitations arise depends on whether the transmembrane potential gradient across the border spans the threshold for regenerative depolarization (Cheng, Mowrey, Van Wagoner, Tchou & Efimov, 1999). The finding of break excitations, combined with the fact that positive VEP can result in "make" excitations (where "make" refers to the onset of a shock) in regions where tissue is at or near diastole, resulted in a novel understanding of how a strong stimulus can trigger the development of new activations.…”
Section: Current Understanding Of Defibrillation Mechanismsmentioning
confidence: 99%
“…All factors depend, ultimately, on shock strength. Increasing shock strength results in higher voltage gradients across borders between regions of opposite polarity, leading to more break-excitations (Cheng, Mowrey, Van Wagoner, Tchou & Efimov, 1999) which then start to traverse the post-shock excitable gap earlier (Skouibine et al, 2000a) and at a faster velocity (Cheng, Mowrey, Van Wagoner, Tchou & Efimov, 1999), as well as extending refractoriness to a larger degree (Knisley et al, 1994).…”
Section: Current Understanding Of Defibrillation Mechanismsmentioning
confidence: 99%
“…Experimental studies demonstrated that shock might induce virtual electrodes (Kinsley et al, 1994;Wikswo JP et al, 1995;Fast et al, 2002;Sharifov et al, 2004). The picture was completed with the computer simulation methods (Efimov et al, 1997;Efimov et al 1998;Cheng et al, 1999;Efimov et al, 2000a;Efimov 2000b;Zemlin et al, 2006). Virtual electrode can create singularity points by closing an electrical circle through electrically conducting tissue.…”
Section: Wwwintechopencommentioning
confidence: 99%